Empowering Early Childhood Education Teachers through digital early literacy assessment program - Martha Christianti; Nur Hayati; Nur Cholimah; Ika Budi Maryatun; Rosida Nur Kasanah; Yovinka Agista Putri; Firqotul Arifah; Bima Putro Wijayanto; Sazliana Idmi Martuaji; F Devi Kurnia (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
This community service program addressed the limited capacity of early childhood education (PAUD) teachers to conduct systematic and contextual initial literacy assessments. The program aimed to improve teacher competence through practice-based training and mentoring supported by digital application technology. It was implemented at PAUD Kampung Emas, Krapyak, Sleman, Yogyakarta, involving 20 PAUD institutions and 33 teachers, and was conducted in three stages: needs identification, training, and evaluation. The results showed an increase in teachers’ assessment comprehension scores from 58 to 88 percent, with monitoring indicating that 46.7 percent of teachers were able to independently implement the assessment while others still required technical assistance. Overall, the program improved assessment quality and promoted data-based learning practices, demonstrated strong potential for sustainable replication with contextual adjustments, and supported cross-institutional collaboration to enhance the quality of early childhood education in Indonesia. Furthermore, the success of this initiative demonstrates that integrated training and technological support effectively shift teacher paradigms, repositioning assessment as a vital tool for instructional development rather than a mere administrative obligation.